2009
DOI: 10.1002/lary.20706
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy in the elderly population: Does age really matter?

Abstract: Nearly 700 parathyroidectomies were performed at our institution over 10 years. Elderly patients comprised one third of this population. They were likely to have longer hospital and recovery room stays, and postoperative normocalcemia with elevated PTH, which may actually be a normal finding for these patients, but it warrants further study. The rate, timing, and types of complications were similar between age groups, although elderly patients had more cardiac complications. When properly indicated, parathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Program Study" found no difference in post-surgical complications between patients >80 years and those <60 years (25). Similarly, another study reported comparable complication rates for ≥65-year old patients undergoing parathyroidectomy when compared to younger ones (21). A more previous study also underlines our findings by reporting similar rates for surgical re-explorations and postoperative complications between <70-year-old patients and patients ≥70 years (19).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Program Study" found no difference in post-surgical complications between patients >80 years and those <60 years (25). Similarly, another study reported comparable complication rates for ≥65-year old patients undergoing parathyroidectomy when compared to younger ones (21). A more previous study also underlines our findings by reporting similar rates for surgical re-explorations and postoperative complications between <70-year-old patients and patients ≥70 years (19).…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have reported conflicting findings concerning PTX-safety in elderly patients (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, patients who undergo PTx by either strategy are hospitalized for between 4 and 24 hours postoperatively with patients undergoing BNE more frequently admitted for an overnight observation. Multiple studies have found that elderly patients have significantly longer post-PTx hospitalizations compared with younger patients, although lengths of stay were not clearly defined by type of operation (BNE versus MIP) [52, 53]. Although two studies reported that same-day discharge is half as likely in elderly versus younger patients at the same institutions [52, 53], other studies found no difference [9, 14, 43].…”
Section: Anesthesiamentioning
confidence: 99%
“…Multiple studies have found that elderly patients have significantly longer post-PTx hospitalizations compared with younger patients, although lengths of stay were not clearly defined by type of operation (BNE versus MIP) [52, 53]. Although two studies reported that same-day discharge is half as likely in elderly versus younger patients at the same institutions [52, 53], other studies found no difference [9, 14, 43]. Recent shortened lengths of stay in all patients have been attributed to the introduction of minimally invasive techniques [50, 52].…”
Section: Anesthesiamentioning
confidence: 99%
See 1 more Smart Citation